The 'leaped advancement of industry' and the 'resound of lamentations': A philosophical, historical, and sociological introduction to 'existential threats' - Spilios, Iason; Vartziotis, Elli Danae; Tympas, Aristotle (Neusis, 2025)
Several of the world’s most renowned universities and research institutions have recently established institutions to study the so-called “existential risks”, which represent threats to the very continuity of life on the planet, “existential threats”. Among others, these include climate change and the environmental crisis in general, artificial intelligence, pandemics and the manipulation of the genetic material. The concept “existential threats” has emerged from interventions in the context of philosophy, with key ones coming from the philosophy of technology. After introducing to such interventions, our article moves on to propose an original connection between existential threats and the history and sociology of technology, with the aim of enriching research on their causes and characteristics.